Are Sustainability Disclosure and Tax Avoidance Associated With Firm Risk? - Syafrudin Bachtiar Ramadhani; Amrie Firmansyah (AFEBI Accounting Review, 2022)
Financial and non-financial information issued by the company can be used as material for investment analysis by investors in the capital market. This study examines the effect of sustainability disclosure and tax avoidance on firm risk. Research data is sourced from financial reports, annual reports, sustainability reports and information on share prices of mining sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. Data obtained from www.idx.co.id, www.idnfinancials.com, www.finance.yahoo.com, and the company's official website. Based on purposive sampling, the total sample used in this study amounted to 56 observations. Hypothesis testing is conducted by using multiple linear regression analysis for panel data. This study suggests that sustainability disclosure is positively associated with corporate risk, while tax avoidance is not associated with firm risk. This research indicates that the Financial Services Authority needs to monitor company activities and policies that can increase company risk to improve investor protection in the Indonesian capital market.